GROWTH PERFORMANCE OF ABERDEEN-ANGUS CALVES DURING THE MILK-FEEDING PERIOD - Abdukarim Nuriddinovich Kochkarov (Modern American Journals, 2025)
This article presents a study on the growth performance of Aberdeen-Angus calves during the milk-feeding period. Parameters such as live weight, average daily gain, general development, and health condition were evaluated. The results confirmed the high genetic potential of the Aberdeen-Angus breed, with intensive growth and strong adaptability in early life. These traits make the breed promising for beef production.
Keywords: Aberdeen-Angus, calves, milk-feeding period, growth performance, live weight, daily gain.